The synergistic relationship between crowdfunding and corporate social responsibility: A case study - Kamal, Mohamad Kamal (European Journal of Islamic Finance, 2020)
Crowdfunding is one of the new financing aspects that technology has added in the past decade and has grown significantly to become an alternative source of finance and assisting business projects and social & environmental initiatives. Despite the development and spread of debt-based Crowdfunding significantly, donation-based crowdfunding is also progressing, especially with the growing relationship between crowdfunding and corporate social responsibility (CSR) and through which it is possible to create opportunities to attract funds by crowdfunding platforms. The aim of this paper is to analyze the relationship between Crowdfunding and the principles of CSR. In particular, the study examines whether the adoption of CSR principles in crowdfunding platforms affects the success of funding and the ability of companies and entrepreneurs to access financial resources on the one hand and whether Crowdfunding is an effective means of financing projects that are in line with the objectives of CSR on the other hand. The approach is based on a qualitative research methodology formed by a case study using data from a crowdfunding platform in Middle East countries to investigate the funds that are raised which are consistent with the principles of CSR taking into account cultural and religious characteristics. The results of the paper show that the presence of CSR positively affects the success of the funding offered and that the crowdfunding platforms are an effective and innovative tool for financing projects that are in line with the objectives of CSR.